How Hedonic Value Mediated Influence of Brand Experience on Brand Equity - Rahayu, Tuti; Siregar, M. Ridha; Kesuma, T. Meldi; Halim, Hendra; Ullya, Raisa (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to assess the impact of brand experience on brand equity, with hedonic value as a mediating factor, among iPhone users in Aceh. The study utilized a sample of 200 iPhone users in Aceh, selected through purposive sampling. Structural Equation Modeling (SEM) was employed as the analytical method to examine the relationships between the variables. The findings indicate that brand experience has a significant impact on both brand equity and hedonic value, while hedonic value also significantly influences brand equity. Additionally, hedonic value was found to partially mediate the relationship between brand experience and brand equity.